Severe Acute Respiratory Syndrome Coronavirus 2 Placental Infection and Inflammation Leading to Fetal Distress and Neonatal Multi-Organ Failure in an Asymptomatic Woman. (26th December 2020) - Schoenmakers, Sam; Snijder, Pauline; Verdijk, Robert M; Kuiken, Thijs; Kamphuis, Sylvia S M; Koopman, Laurens P; Krasemann, Thomas B; Rousian, Melek; Broekhuizen, Michelle; Steegers, Eric A P; Koopmans, Marion P G; Fraaij, Pieter L A; et al.
Abstract : Placental severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with a specific histiocytic intervillositis. Placental fibrin depositions can decrease the maternal-fetal interface causing fetal distress. Coronavirus disease 2019-related placental inflammation can lead to SARS-CoV-2-associated pediatric inflammatory multisystem syndrome. Abstract: Background: In general, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy is not considered to be an increased risk for severe maternal outcomes but has been associated with an increased risk for fetal distress. Maternal-fetal transmission of SARS-CoV-2 was initially deemed uncertain; however, recently a few cases of vertical transmission have been reported. The intrauterine mechanisms, besides direct vertical transmission, leading to the perinatal adverse outcomes are not well understood. Methods: Multiple maternal, placental, and neonatal swabs were collected for the detection of SARS-CoV-2 using real-time quantitative polymerase chain reaction (RT-qPCR). Serology of immunoglobulins against SARS-CoV-2 was tested in maternal, umbilical cord, and neonatal blood. Placental examination included immunohistochemical investigation against SARS-CoV-2 antigen expression, with SARS-CoV-2 ribonucleic acid (RNA) in situ hybridization and transmission electron microscopy. Results: RT-qPCRs of the oropharynx, maternal blood, vagina, placenta, and urine were all positive over a period of 6 days, while breast milk, feces, and all neonatal samples tested negative. Placental findings showed the presence of SARS-CoV-2 particles with generalized inflammation characterized by histiocytic intervillositis with diffuse perivillous fibrin depositions with damage to the syncytiotrophoblasts. Conclusions: Placental infection by SARS-CoV-2 leads to fibrin depositions hampering fetal-maternal gas exchange with resulting fetal distress necessitating a premature emergency cesarean section. Postpartum, the neonate showed a fetal or pediatric inflammatory multisystem-like syndrome with coronary artery ectasia temporarily associated with SARS-CoV-2 for which admittance and care on the neonatal intensive care unit (NICU) were required, despite being negative for SARS-CoV-2. This highlights the need for awareness of adverse fetal and neonatal outcomes during the current coronavirus disease 2019 pandemic, especially considering that the majority of pregnant women appear asymptomatic.